Gigi Căciuleanu: To dance, or not to be… Je suis quelqu’un qui danse! Ludmila Patlanjoglu. « Gigi Căciuleanu – Omul Dans [Gigi Căciuleanu – Dance Man] » Editura Institutului Cultural Român în colaborare cu Editura Nemira, editat cu sprijinul JTI şi al Fun - POENAR, Aura (Studia Universitatis Babeș-Bolyai Dramatica, 2018)
It is not an easy thing to embark upon such an ambitious undertaking as to assemble an account of Gigi Căciuleanu’s universe. And as I refer to the scope of LudmilaPatlanjoglu’s venture by such a vast term, and not life or career, my choice of words is, not by chance, intimidated by the richness of Căciuleanu’s artistic persona that has, from the outset, singled itself as singular in the world of dance and art altogether. I think it would befit Deleuze’s idea of agencement to view the concept behind this book as a multilayered, multifaceted assemblage of images, narratives, voices and gestures. The underlying structure of the book walks us through a complex weaving that works best in this almost cinematic orchestration of voices and gazes meant to seize something of the aura that surrounds the complex and variegated artistic but also very modest, generous, and noble personality of Gigi Căciuleanu.